Social entrepreneurship in higher education: challenges and opportunities. Issue 3 (3rd July 2022) - Roslan, Muhammad Hamirul Hamizan; Hamid, Suraya; Ijab, Mohamad Taha; Yusop, Farrah Dina; Norman, Azah Anir
ABSTRACT: Social entrepreneurship (SE) had been introduced in the university as one of the efforts to nurture future social entrepreneurs. SE courses established at the university level with a combination of cooperation from the local community and industry give a more effective impact on the local community. The knowledge and skills taught from universities regardless of the academic or cultural background can be used to balance the social problems in the community with the development of social innovation to solve the issues. However, several challenges delayed further development of a successful SE programme in higher education. This research employs the systematic literature review (SLR) which utilizes in-depth and absolute evaluation of related literature on the research topic. Four challenges have been encountered include; the design of SE curricula, financial and funding problems, lack of professionals to teach SE courses, and prohibitive social and university environment issues. This research has also suggested some best practices include; more SE awareness programmes, university management in solving funding problems, preparing SE coaching professionals, and setting up more university-industry collaborations. This paper proposes suggestions to counter the challenges and leverage the social network as an innovative technological alternative and giving more opportunities for improved social benefits.